EKONOMI POLITIK DALAM ISLAM (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This article explain about the contemporary works of  Islamic studies, especially in connection with the issues of  Islamic economy and politic. The economic and politic issues in Islamic system would be an easy to apply the process if  there was a consensus among Moslem scholars. Unfortunately, it is very difficult to find the consensus, so the article just discuss the important controversies about it. After understanding  well that the Islamic state theoretically is a legal enity, the writer tries to study on the structure of economy and politic in Islamic system. The benefit way and often used is comparing between  the Islamic system and socialism as theoretical entities. This way is used in  framework  as  written above. Following the consensus of the scholars, the successful of an Islamic state depends on its capacity in creating the Islamic mechanism, especially in relation with preceptor mechanism.